2007
DOI: 10.1093/molehr/gam090
|View full text |Cite
|
Sign up to set email alerts
|

Changes in transcription profile and cytoskeleton morphology in pelvic ligament fibroblasts in response to stretch: the effects of estradiol and levormeloxifene

Abstract: Failure of ligamentous support of the genital tract to resist intra-abdominal pressure is a plausible underlying mechanism for the development of pelvic organ prolapse, but the nature of the molecular response of pelvic tissue support remains unknown. We hypothesized that the expression of genes coding for proteins involved in maintaining the cellular and extracellular integrity would be altered as a result of mechanical stretch. Therefore, cDNA microarrays were used to examine the difference in transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…Ewies demonstrated recently that mechanical stretch disturbs the fibroblasts' ability to maintain the cytoskeleton architecture. The use of estrogens did not reverse the process or protect the cells from the effect of stretch, but significantly increased the rate of fibroblast proliferation, suggesting their role in the healing process [62].…”
Section: The Fibroblast In Popmentioning
confidence: 91%
“…Ewies demonstrated recently that mechanical stretch disturbs the fibroblasts' ability to maintain the cytoskeleton architecture. The use of estrogens did not reverse the process or protect the cells from the effect of stretch, but significantly increased the rate of fibroblast proliferation, suggesting their role in the healing process [62].…”
Section: The Fibroblast In Popmentioning
confidence: 91%
“…23 Several studies have also demonstrated modified fibroblast responses in prolapse. [41][42][43][44] Several authors have analysed the expression of collagen regulators (MMP and TIMP) ( Table 2). Expression of MMP-1,-2 and -9 is increased in women with prolapse, demonstrating more collagen breakdown with loss of tissue integrity.…”
Section: Regulators Of Collagenmentioning
confidence: 99%
“…Alterations in the quantity and quality of collagen, morphology of connective tissue after menopause, and experimental evidence that estrogen modulates the collagen metabolism, strongly indicate the involvement of estrogens in the pathogenesis of pelvic organ prolapse [12]. It is also believed that the appearance of prolapse and mechanical stretch disturb the fibroblast's ability to maintain the cytoskeleton architecture and quality of the extracellular matrix [13]. In addition, estrogen has been shown to decrease tissue-degrading matrix metalloproteinases in fibroblasts derived from pelvic floor connective tissue.…”
Section: Discussionmentioning
confidence: 99%